Exploring the effectiveness of tawheed-based programmes for rehabilitating drug addicts in Madrasah Khairul Insan,Terengganu - Nurul Nazirah Nazir (2021)
This research sought to explore the effectiveness of tawheed-based programmes to rehabilitate drugs addicts in Madrasah Khairul Insan (MKI) which is located at Kampung Jenagor, Hulu Terengganu. Another primary focus of this study was to identify the perceived achievement attained by this centre, apart from determining the challenges it faced. Additionally, the study aimed to assess the relevance of implementing MKI's programme to other centres around Malaysia. A total of six respondents (two management members and four residents of the centre, all male) were drawn by using purposive sampling. The interview was developed as an instrument to collect data. The findings indicated the effectiveness of the programme which has been run in MKI for almost 25 years.